Development of Culturally Responsive Teaching-Based Modules on Plant Structure and Function Material to Improve the Ecoliteracy of Junior High School Students in Jember - Azizah, May linda Nur; Handayani, Rif’ati Dina; Hariani, Sulifah Aprilya (FKIP Universitas Lampung, 2024)
Abstract: This study aims to determine the validity and effectiveness of the Culturally Responsive Teaching-based science module in improving the ecoliteracy of junior high school students in Jember Regency. The subjects in this study were students of class VIII F SMPN 1 Ajung totaling 31 students, with 17 male students and 14 female students. The research model used in this study is the 4-D (Four D) development model which consists of four stages including define, design, develop, and disseminate. The instruments in this study were interview guidelines, validation sheets, and pre-test and post-test sheets for students. The validity data analysis was obtained through a validation questionnaire validated by three expert validators, and the effectiveness data analysis was obtained through the results of the pre-test and post-test given to students at the time before the application of the Culturally Responsive Teaching-based science module and at the time after the application of the Culturally Responsive Teaching-based science module. The validity results of this study obtained an average assessment score from the three expert validators of 94% with very valid criteria so that culturally responsive teaching-based modules can be applied to science learning. The results of the effectiveness of culturally responsive teaching-based modules produce an average N-Gain value at SMPN 1 Ajung of 0.85 with high-value criteria so that students can increase student ecoliteracy. Based on the research results, it is concluded that developing culturally responsive teaching-based modules is valid and effective in improving students' ecoliteracy. Keywords: culturally responsive teaching, ecoliteracy, learning module. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp329-340